Alteration of forest structure and ecosystem function along the Yampa River, Colorado - Richter, Holly E., author; Leininger, Wayne, advisor; Carpenter, Alan, committee member; Wohl, Ellen E., committee member; Scott, Michael L., committee member (Colorado State University. Libraries, 1999)
The hydrologic regime of the Yampa River remains relatively unaltered, supporting some of the finest examples of riparian community types left in the Upper Colorado River Basin. However, GIS analyses suggest that the existing stands of riparian vegetation represent only a fraction of that which likely spread across the Yampa's floodplain only a century before. Anglo settlement has resulted in clearing of riparian plant communities for agricultural uses, and in extensive thinning and fragmentation of the remaining stands of forest. Previously thinned forests were found to exhibit a mixed-age stand structure as a result of subsequent asexual reproduction by Populus angustifolia. This research examines the complex interactions between natural hydrologic and geomorphic processes and vegetation patterns within the floodplain ecosystem through the use of an ecological model. To effectively conserve the biodiversity represented within particular ecosystems, ecologists need to develop a better understanding of natural ecosystem function and the ways in which human-induced stresses have altered these systems. The model provided a tool by which biotic, hydrologic, and geomorphic data could be integrated to create testable hypotheses regarding ecosystem dynamics. Interpretation of modeling results suggests that in the vicinity of the study site, the Yampa River may be especially vulnerable to human alteration due to its geomorphic and hydrologic characteristics. In recent decades, both increases in floodpeak variability, and human clearing of riparian forest cover that has decreased streambank stability, have likely contributed toward changing trends in ecosystem function and the regeneration of riparian communities. Model development not only led to the formation of hypotheses regarding the complex interactions between ecosystem structure and function (including complex feedback mechanisms), but also helped to define preliminary site conservation goals. An adaptive management approach will be used to test the hypotheses suggested by this model in the future. Finally, a strategy for maximizing the asexual reproduction of Populus angustifolia along the Yampa River was developed as a critical first step toward the development of a larger ecosystem restoration program.
Keywords: ecology; botany; hydrology; geography; hydrologic sciences; physical geography